Cystic Lymphangioma of the Chest Wall in a 5-Year-Old Male Patient: A Rare and Atypical Localization—A Case Report and Comprehensive Review of the Literature - Dimitrios Patoulias; Ioannis Patoulias; Christos Kaselas; Maria Kalogirou; Chatzopoulos Kyriakos; Farmakis Konstantinos; Thomas Feidantsis; Papacrivou Eleni (Case Reports in Pediatrics)
Lymphangioma is a benign congenital malformation. The extremely rare and atypical localization of a lymphangioma in the chest wall was the real motive for the present case study. A 5-year-old boy was admitted to the Emergency Department of the 1st Department of Pediatric Surgery, Aristotle University of Thessaloniki, due to the presence of a mildly painful swelling in the left lateral chest wall, which was first noticed three months ago, after a blunt injury during sport. Physical examination revealed the presence of a palpable, spherical, painful, nut-sized subcutaneous lesion in the left lateral chest wall, respectively, with the anterior axillary line, at the height of the 6th to 7th intercostal space. Presence of ecchymosis on the overlying skin was also noticed. During palpation, we did not notice fluctuation, while transillumination was not feasible. Performance of ultrasonography, including Doppler color flow imaging, followed, depicting a subcutaneous cystic lesion, 2.1⁎3.2 cm in dimensions, without extension to the thoracic cavity. Scheduled surgical excision of the lesion was decided. Histopathological examination documented the diagnosis of cystic lymphangioma. Patient is still followed up on a 6-month basis. He remains asymptomatic, after 2 years, without indication of relapse.